NK cell upraise in the dark world of cancer stem cells - Alireza Shokouhifar; Javad Firouzi; Masoumeh Nouri; Gholamreza Anani Sarab; Marzieh Ebrahimi (Cancer Cell International, 2021)
Abstract One of the obstacles in treating different cancers, especially solid tumors, is cancer stem cells (CSCs) with their ability in resistance to chemo/radio therapy. The efforts for finding advanced treatments to overcome these cells have led to the emergence of advanced immune cell-based therapy (AICBT). Today, NK cells have become the center of attention since they have been proved to show an appropriate cytotoxicity against different cancer types as well as the capability of detecting and killing CSCs. Attempts for reaching an off-the-shelf source of NK cells have been made and resulted in the emergence of chimeric antigen receptor natural killer cells (CAR-NK cells). The CAR technology has then been used for generating more cytotoxic and efficient NK cells, which has increased the hope for cancer treatment. Since utilizing this advanced technology to target CSCs have been published in few studies, the present study has focused on discussing the characteristics of CSCs, which are detected and targeted by NK cells, the advantages and restrictions of using CAR-NK cells in CSCs treatment and the probable challenges in this process.